Complex Catalytic Materials Based on the Perovskite-Type Structure for Energy and Environmental Applications - Andrei, Florin (Materials (Basel), 2020)
This review paper focuses on perovskite-type materials as (photo)catalysts for energy and environmental applications. After a short introduction and the description of the structure of inorganic and hybrid organic-inorganic perovskites, the methods of preparation of inorganic perovskites both as powders via chemical routes and as thin films via laser-based techniques are tackled with, for the first, an analysis of the influence of the preparation method on the specific surface area of the material obtained. Then, the (photo)catalytic applications of the perovskites in energy production either in the form of hydrogen via water photodecomposition or by methane combustion, and in the removal of organic pollutants from waste waters, are reviewed.